FEEDING OF BREEDING YOUNG CATTLE (Multidisciplinary Journal of Science and Technology, 2024)
This article is devoted to give information about Feeding breeding young cattle, particularly in the context of beef or dairy production which is crucial for their growth, health, and future productivity.